Application of heat pump drying technology to produce dried mango products from Tu Quy mango (Mangifera india L.), Vietnam, on a pilot scale - Thao, Bui Thi Thu; Thanh Hung, Pham; Lai, Ngoc Dung; Tran, Thi Yen Nhi; Nguyen, Ngoc Quy; Pham, Tri Nhut; Truc Tran, Thanh; Giang Bach, Long; Dao, Tan Phat (Frontiers in Sustainable Food Systems, 2024)
In this study, the heat pump drying technique was applied to develop the production process of dried mango from Tu Quy mango sources, Ben Tre province, Vietnam. The experiment was performed in three steps. First, mango slices were treated through the blanching process. Samples were pretreated with size from 6 to 12 mm at 80-95°C for 3-6 min, and then the mango slices were soaked in the syrup solution concentration range of 25- 40°Bx, citric acid of 0.5-2% and of glycerol 0.1-0.4% at 35-65°C for 90-180 min. Finally, the samples were dried using a pilot-scale heat pump dryer until the moisture content reached 14-16%. The results showed that the blanching and osmosis processes were carried out under optimal conditions to inactivate the PPO enzyme, obtain maximum polyphenol compounds, and conform to the product appearance. Besides, the drying process was carried out at 30°C for 1080 min with the polyphenol content retaining 11.71 mgGAE/gDW—successful research in building production processes, and diversifying products from mango. Technological processes use innovations that improve product quality in terms of quantity and quality. Furthermore, the manufacturing process was carried out on a pilot device which facilitates the synchronization of large-scale production processes easily. Improve the economic value and solve the problem of congestion which is the current situation of the mango industry in Vietnam today.